Penerapan Model pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas I Materi Ungkapan Terimakasih, Maaf dan Tolong di SDN Banjarsugihan V/617 Surabaya - Tri Murtiningsih (Universitas Lampung, 2023)
This study aims to determine the increase in activity and learning outcomes of Indonesian language students in grade I at SDN Banjarsugihan V/617, Surabaya, use Project Based Learning (PjBL) learning. This researhed is a classroom action research carried out for two cycles conducted an class I SDN Banjarsugihan V/617 many as 26 students.Cycle I shows the completeness of student learning activities reaching 74.78% and student learning outcomes of 58%. In cycle II, student learning activities increased to 85.89%, while students learning outcomes achieved 88%. Based on the results of the research above, it can be concluding that the use of Project Based Learning (PjBL) learning can increase activities and learning outcomes of Indonesian language material for expressions of thanks, sorry and help class I students at SDN Banjarsugihan V./617 Surabaya semester I 2022-2023 school years. Keywords: Project Based Learning (PjBL), learning outcomes, Learning Activities